2013
DOI: 10.1089/cap.2012.0085
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Gains from Including Both Dextroamphetamine and Methylphenidate in Stimulant Trials

Abstract: The likelihood of a favorable response and optimal response strength is increased by including both stimulants in the stimulant trial. The study was first registered in clinical trials 28 September 2010. Clinical Trials.gov Identifier: NCT01220440.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
1
18
0
1
Order By: Relevance
“…Adverse events in relation to the best drug are a primary concern, because this is the stimulant condition most likely to be selected for longterm treatment. The assessment of best drug for individual children was based on an ADHD questionnaire rated by parents and teachers, and a change from placebo to each of four stimulant conditions were calculated, using standard effect size values, and categorized either as ''no favorable response'' (no change, deterioration), ''mild favorable response,'' or ''strong favorable response'' accordingly (Ramtvedt et al 2013). Finally, differences between the two stimulants in terms of the load of adverse events they produced in individual children were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse events in relation to the best drug are a primary concern, because this is the stimulant condition most likely to be selected for longterm treatment. The assessment of best drug for individual children was based on an ADHD questionnaire rated by parents and teachers, and a change from placebo to each of four stimulant conditions were calculated, using standard effect size values, and categorized either as ''no favorable response'' (no change, deterioration), ''mild favorable response,'' or ''strong favorable response'' accordingly (Ramtvedt et al 2013). Finally, differences between the two stimulants in terms of the load of adverse events they produced in individual children were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of methylphenidate use in school-aged children, however, outnumbers prescriptions of amphetamine products by > 100:1 across the Nordic countries (Zoega et al 2011), and a marked imbalance in prescribing patterns for the two classes of stimulants for the treatment of ADHD is also the case in the United Kingdom (Hodgkins et al 2012). Such a bias indicates that amphetamine products seldom are tried despite the fact that studies employing single-subject analyses to compare methylphenidate and dextroamphetamine consistently show that the inclusion of both stimulants optimizes the reduction of ADHD symptoms and may contribute to a reduction in adverse events (Arnold et al 1978;Pelham et al 1990;Elia et al 1991;Green 1996;Efron et al 1997a,b;O'Malley et al 2000;Ramtvedt et al 2013). Utilizing the availability of both stimulants fully may potentially enhance treatment continuation that is found to be affected by both the beneficial outcome and the load of adverse events associated with the treatment (Toomey et al 2012).…”
mentioning
confidence: 99%
“…The study included a 6-month baseline period prior to the index date, and patients were followed for a 12-month period post-index ( Figure 1). Patients were grouped by age as children (aged 6-12) and adolescents (aged [13][14][15][16][17].…”
Section: Methodsmentioning
confidence: 99%
“…the Suboptimal Response Prediction [SRP] Model) was adapted and applied to assess the risk of medication discontinuation with or without switching, augmentation, and ADHD-related total costs among patients initiating OROS-MPH or LDX. Crossover studies in children and in adolescents with ADHD have demonstrated that treatment response to stimulants varies on an individual basis 17,18 ; however, further investigation is needed to identify factors associated with ADHD treatment response. This analysis investigated if allocation of ADHD treatment by risk groups could result in better outcomes for children and adolescents receiving care within the Texas Medicaid system.…”
Section: Introductionmentioning
confidence: 99%
“…Antallet vitenskapelige studier på medisineffekter ved AD/HD er meget høyt. Positive effekter i form av reduksjon i AD/HD-symptomer på kort og mellomlang sikt, opptil fem år, er godt dokumentert (2)(3)(4). Langtidseffekter av en spesifikk behandling er generelt vanskelig å dokumentere.…”
unclassified